XFEL Crystal Structures of Peroxidase Compound II. (19th May 2021) - Kwon, Hanna; Basran, Jaswir; Pathak, Chinar; Hussain, Mahdi; Freeman, Samuel L.; Fielding, Alistair J.; Bailey, Anna J.; Stefanou, Natalia; Sparkes, Hazel A.; Tosha, Takehiko; Yamashita, Keitaro; Hirata, Kunio; et al.
Abstract: Oxygen activation in all heme enzymes requires the formation of high oxidation states of iron, usually referred to as ferryl heme. There are two known intermediates: Compound I and Compound II. The nature of the ferryl heme—and whether it is an Fe IV =O or Fe IV ‐OH species—is important for controlling reactivity across groups of heme enzymes. The most recent evidence for Compound I indicates that the ferryl heme is an unprotonated Fe IV =O species. For Compound II, the nature of the ferryl heme is not unambiguously established. Here, we report 1.06 Å and 1.50 Å crystal structures for Compound II intermediates in cytochrome c peroxidase (C c P) and ascorbate peroxidase (APX), collected using the X‐ray free electron laser at SACLA. The structures reveal differences between the two peroxidases. The iron‐oxygen bond length in C c P (1.76 Å) is notably shorter than in APX (1.87 Å). The results indicate that the ferryl species is finely tuned across Compound I and Compound II species in closely related peroxidase enzymes. We propose that this fine‐tuning is linked to the functional need for proton delivery to the heme. Abstract : Enzymatic fine‐tuning of heme reactivity: Free‐electron laser crystal structures of two different heme‐containing peroxidases—cytochrome c peroxidase and ascorbate peroxidase—show differences in the nature of the ferryl species. Precise enzymatic fine‐tuning within structurally similar heme active sites is implicated.